Concept Map in Medical Education: Visualization in Medical Education through Concept Mapping. - Javed, Kainat; Aslam, Kinza; Jawaad, Imran; Leghari, Sadia Irshad; Leghari, Qurat-Ain (Journal of Rawalpindi Medical College, 2024)
Objective: To assess and compare the proficiency of concept mapping skills among resident doctors of varying experience levels (1st, 2nd, 3rd, and 4th-year residents) before any instruction. This shift aims to produce more effective doctors who can comprehensively grasp diseases. Pakistani medical colleges have adopted these teaching reforms to enhance students' cognitive skills, encouraging them to apply knowledge to clinical scenarios for better decision-making. Method: The study was conducted among 21 resident doctors in a pediatric unit of a public hospital, spanning from January 1st to August 31st, 2022. All participants, comprising 1st-year residents (5), 2nd-year residents (7), 3rd-year residents (5), and 4th-year residents (4), provided informed consent. Initially, participants underwent a concept mapping training session and created a concept map of diarrhoea as a baseline assessment. Subsequently, they completed a 3-session diarrhoea course. After this instruction, they were tasked with creating a post-instruction concept map of diarrhoea. Results: the study highlights the positive impact of education on concept mapping skills, particularly among 3rd and 4th-year residents, underscoring the potential for enhancing medical education strategies. Conclusion: In conclusion, this study conducted among resident doctors in a pediatric unit investigated the impact of concept mapping training and a diarrhoea education program on their concept mapping skills. The findings revealed significant differences between 1st-year residents and their more experienced counterparts, with 3rd and 4th-year residents demonstrating more complex concept maps.